On becoming a skilled migrant: towards habitus transformation through higher education - Thondhlana, Juliet (2018)
Research on the labour market experiences of highly skilled migrants has revealed the crippling employability challenges they face in the UK workplace resulting from the devaluation of their homeland qualifications and experiences. Studies on highly skilled migrants from Zimbabwe have revealed how migrants have to resort to semi-skilled and unskilled work for survival. Little is known, however, about the education and labour market experiences of migrants who come into the UK without degrees and subsequently acquire a UK degree. Drawing on Bourdieu’s theory of cultural capital and habitus, this article explores the higher education and labour market experiences of this group, as revealed by in-depth interviews with 20 participants. Findings reveal that these participants’ habitus is a complex dynamic interaction of diverse (pre)dispositions and strategies which result in them reporting better labour market success than Zimbabwe-degreed migrants. Arguably, their experiences suggest the emergence of a new UK-based habitus for Zimbabwean migrants.